Balancing dilemmas in assessment and learning in contemporary education [ - Havnes, Anton , 1951-; McDowell, Liz (Routledge research in education ;, 2008)
Illustrates the conceptual and practical dilemmas of assessment and raises issues that are relevant and applicable across a variety of modes of assessment and across various contexts where assessment